2004
DOI: 10.1016/j.femsec.2004.03.015
|View full text |Cite
|
Sign up to set email alerts
|

The role of microbial community composition and groundwater chemistry in determining isoproturon degradation potential in UK aquifers

Abstract: The community response of indigenous sandstone, chalk and limestone groundwater microorganisms to the addition of the commonly used herbicide isoproturon was examined. The addition of 100 microg l(-1) isoproturon generally caused an increase in species diversity determined by chemotaxonomic analysis (fatty methyl ester analysis) of isolates resulting from incubation of cultures at 18 degrees C for 4 days. Amongst the groundwater samples to which isoproturon was added, isoproturon degradation rates were correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Some findings suggest no correlation (e.g. Johnson et al 2000) whereas others identify enhanced biodegradation when there has been previous exposure to, for example, isoproturon (Johnson et al 1998(Johnson et al , 2000(Johnson et al , 2004 or BTEX (Fahy et al 2006). The key factors determining whether a bacterial community can degrade pollutants appear to be the makeup of the community itself and the groundwater chemistry (Johnson et al 2004).…”
Section: Microbial Communities In Uk Aquifersmentioning
confidence: 99%
See 4 more Smart Citations
“…Some findings suggest no correlation (e.g. Johnson et al 2000) whereas others identify enhanced biodegradation when there has been previous exposure to, for example, isoproturon (Johnson et al 1998(Johnson et al , 2000(Johnson et al , 2004 or BTEX (Fahy et al 2006). The key factors determining whether a bacterial community can degrade pollutants appear to be the makeup of the community itself and the groundwater chemistry (Johnson et al 2004).…”
Section: Microbial Communities In Uk Aquifersmentioning
confidence: 99%
“…The key factors determining whether a bacterial community can degrade pollutants appear to be the makeup of the community itself and the groundwater chemistry (Johnson et al 2004). Johnson et al (2004) found that the presence of isoproturon changed the community structure, and degradation was accompanied by an increase in the proportion of a few dominant species, although different degrading taxa were found in different samples. This suggests that there is some flexibility in the community composition (functional redundancy) and that some functions can be carried out by different organisms.…”
Section: Microbial Communities In Uk Aquifersmentioning
confidence: 99%
See 3 more Smart Citations